An analysis of scheduling scheme for QoS guaranteed interactive multimedia over high speed wireless campus networks - Alam, M.K.; Abd Latif, Suhaimi; Masud, Mosharrof Hussain; Akter, Mahmuda (2013)
Interactive Multimedia (IMM) applications have observed quick growth in the world of computer and communication technologies. Voice, video conferencing, graphics services are considered as IMM applications, at low cost with more flexibility in a high speed Wireless Local Area Network (WLAN) that can be defined as a high speed Wireless Campus Network (WCN). The networks' traffic flow determines the participating users work as a sender or receiver during the voice or video conversation. The IMM applications have to be kept the least data loss and maximum throughput over WCN. Packets scheduling and channel allocation mechanism are the challenging issues for improving IMM transmission and it is still an unresolved problem over WCN. This paper reviews on different exist scheduling mechanisms and channel allocation algorithms of IMM related to various applications and highlights the current issues. A new priority based scheduling scheme and dynamic channel allocation mechanisms have been proposed in this paper. It is expected that the proposed mechanisms ensure the minimum requirement of the IMM applications which will deliver QoS with the least handoff delay and minimize the call dropping probabilities for IMM applications though WCNs.